Application of 2-Dimensional Coil Detector for the Sensitive Direct Salmonella Detection on Plastic Board. (7th July 2017) - Liu, Yuzhe; Du, Songtao; Horikawa, Shin; Chen, I-Hsuan; Chai, Yating; Wikle, Howard Clyde; Suh, Sang-Jin; Chin, Bryan Allen
Abstract : To avoid food contaminated by pathogens such as Salmonella, magnetoelastic biosensors were used for rapid, wireless, and on-field detection. This paper demonstrates a series of measurements from low to high concentration of Salmonella typhimurium on a polyethylene (PE) chopping board by using a highly sensitive surface-scanning system. In this research, two-dimensional planar spiral coils were fabricated and utilized as the surface scanning detectors in the measurement system for the rapid and sensitive detection of Salmonella . ME biosensors, which was made by metallic glass (Metglas alloy 2826MB) with great magnetoelastic properties were applied on the sample surface for the real-time and in-situ measurement process. The resonant frequency changes of different measurement sensors (coated with E2 phage) change with the various of the Salmonella concentration. At the same time, the stability of control sensors (coated with blocking only) confirmed the specific binding of Salmonella typhimurium by the E2 phage.